Xanthomonas citri ssp. citri requires the outer membrane porin OprB for maximal virulence and biofilm formation. (27th July 2016) - Ficarra, Florencia A.; Grandellis, Carolina; Galván, Estela M.; Ielpi, Luis; Feil, Regina; Lunn, John E.; Gottig, Natalia; Ottado, Jorgelina
Summary: Xanthomonas citri ssp. citri (Xcc) causes canker disease in citrus, and biofilm formation is critical for the disease cycle. OprB (Outer membrane protein B) has been shown previously to be more abundant in Xcc biofilms compared with the planktonic state. In this work, we showed that the loss of OprB in an oprB mutant abolishes bacterial biofilm formation and adherence to the host, and also compromises virulence and efficient epiphytic survival of the bacteria. Moreover, the oprB mutant is impaired in bacterial stress resistance. OprB belongs to a family of carbohydrate transport proteins, and the uptake of glucose is decreased in the mutant strain, indicating that OprB transports glucose. Loss of OprB leads to increased production of xanthan exopolysaccharide, and the carbohydrate intermediates of xanthan biosynthesis are also elevated in the mutant. The xanthan produced by the mutant has a higher viscosity and, unlike wild‐type xanthan, completely lacks pyruvylation. Overall, these results suggest that Xcc reprogrammes its carbon metabolism when it senses a shortage of glucose input. The participation of OprB in the process of biofilm formation and virulence, as well as in metabolic changes to redirect the carbon flux, is discussed. Our results demonstrate the importance of environmental nutrient supply and glucose uptake via OprB for Xcc virulence.